Gastric lymphoma and gastric tuberculosis: A diagnostic dilemma - Jain, Atul; Yadav, Pradhuman; Dey, Subhajeet; Karim, Tanweer (Indian Journal of Medical and Paediatric Oncology, 2019)
Gastric outlet obstruction may be caused by a heterogeneous group of diseases that include both benign and malignant conditions. Primary gastric lymphoma (3%–5% of all gastrointestinal malignancies) and primary gastric tuberculosis (TB) (0.4%–2%) are very rare and resemble each other in clinical presentation with diagnostic dilemma between them. Do the two entities exist concomitantly or precede each other is still a topic of debate in the literature. Here, we present a case of primary gastric TB and gastric lymphoma in the same patient.
Keywords: Gastric lymphoma; gastric tuberculosis; immune deficiency